The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15585/mmwr.mm7010e3
|View full text |Cite|
|
Sign up to set email alerts
|

Association of State-Issued Mask Mandates and Allowing On-Premises Restaurant Dining with County-Level COVID-19 Case and Death Growth Rates — United States, March 1–December 31, 2020

Abstract: , this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr). CDC recommends a combination of evidence-based strategies to reduce transmission of SARS-CoV-2, the virus that causes COVID-19 (1). Because the virus is transmitted predominantly by inhaling respiratory droplets from infected persons, universal mask use can help reduce transmission (1). Starting in April, 39 states and the District of Columbia (DC) issued mask mandates in 2020. Reducing person-to-person interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 9 publications
(13 reference statements)
2
124
2
Order By: Relevance
“…As community businesses begin to reopen, these findings underscore the importance of businesses and individuals adhering to public health prevention and mitigation guidelines to reduce additional community transmission, including isolation after receipt of a COVID-19 diagnosis and while experiencing COVID-19-like symptoms, even as vaccination efforts expand. Similar gatherings that involve eating or drinking, such as onpremises dining at restaurants, weddings, and night clubs, have been associated with increased risk for acquiring COVID-19 and have the potential to become super-spreading events for SARS-CoV-2 infection (4)(5)(6)(7)(8). This investigation further demonstrates that inconsistent mask use and inadequate physical distancing in an indoor environment can increase transmission risk** (9,10).…”
Section: Discussionmentioning
confidence: 73%
“…As community businesses begin to reopen, these findings underscore the importance of businesses and individuals adhering to public health prevention and mitigation guidelines to reduce additional community transmission, including isolation after receipt of a COVID-19 diagnosis and while experiencing COVID-19-like symptoms, even as vaccination efforts expand. Similar gatherings that involve eating or drinking, such as onpremises dining at restaurants, weddings, and night clubs, have been associated with increased risk for acquiring COVID-19 and have the potential to become super-spreading events for SARS-CoV-2 infection (4)(5)(6)(7)(8). This investigation further demonstrates that inconsistent mask use and inadequate physical distancing in an indoor environment can increase transmission risk** (9,10).…”
Section: Discussionmentioning
confidence: 73%
“…Regardless of the precise mechanisms of mitigation, observational data from the US and Germany have shown that regions with mask mandates have had a lower impact from SARS-CoV-2 12. Countries with early adoption of face coverings for the public also achieved an earlier acceptance of a social norm during the pandemic 13…”
Section: Yes—babak Javid Dirk Bassler Manuel B Bryantmentioning
confidence: 99%
“…Face mask mandates and usage lead to lower rates of covid-19 cases and deaths (Mitze et al, 2020;Joo et al, 2021;Guy et al, 2021).…”
Section: Accepted Manuscriptmentioning
confidence: 99%